Экспериментальное обоснование термодинамического прогнозирования редокс-взаимодействия микроорганизмов с металлами-окислителями (Hg^2+, CrO4^2− и Cu^2+) - Таширев, А.Б.; Матвеева, Н.А.; Таширева, А.А.; Романовская, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The growth of chemoorganotrophic microorganisms at ultrahigh concentrations of toxic metals-oxidizers (Hg^2+, Cr4^O2− , and Cu^2+) is possible owing to a manifold increase in the concentration of metals (from 1 • 10−8 up to 1.0 mole/l) causes increasing their standard redox-potential (Eo) only by 200. . .400 mV, which stays in a zone of thermodynamic stability of water (−414 mV 6 Eh 6 +814 mV). Microorganisms of the granulated biocatalyst and Antarctic soil microorganisms are capable to grow in the presence of 500 . . . 1000 ppm Hg (II), 5000. . .60000 ppm Cr(VI), and 1000. . .10000 ppm Cu(II). High values of redox-potentials of Hg^2+, CrO4^2− , and Cu^2+ (+920 mV, +555 mV and +440 mV) predetermine the reduction of these metals by alive microorganisms. Microbial reduction of Hg^2+, CrO4^2− , and Cu^2+ leads to the formation of insoluble forms of metals and their sedimentation in solutions. Technogenic associations and the Antarctic soil microorganisms resistant to ultrahigh concentrations of these metals can be used for the development of new environment-protective technologies providing the purification of industrial waste waters from metals in any certain concentration or a wide range of concentrations.